2014
DOI: 10.5296/ber.v4i2.5546
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Financial Leverage on the Profitability in the Tourism Companies (Analytical Study- Tourism Sector- Jordan)

Abstract: This study aims to identify the financial leverage ratio and the rate of return on investment on profitability for sources of the funding in tourism companies which operating in Jordan. And to achieve this study the researcher use some companies related to the Tourism sector from the firms that listed in Amman Stock Exchange.The study finds the existence of a statistically significant impact for the independent variables (financial leverage and ROI) of the Tourism companies on the Profitability. Moreover, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In case of this study, the researchers found out that some researchers have found insignificant relationship between financial leverage and performance and a significant relationship between the two but varying extent. Such studies include: in Nairobi [23] found a negative association between equity to debt ratio (EDR) and Return on equity (ROE).in Jordan [24] in Pakistan [15] who found that financial leverage has a statistically significant inverse impact on profitability at 99% confidence interval; in Tehran, Iran on the relationship among financial leverage and profitability [25]. Other examples include [26] in Thailand and [27] in India who established a positive relationship amid financial leverage and profitability.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In case of this study, the researchers found out that some researchers have found insignificant relationship between financial leverage and performance and a significant relationship between the two but varying extent. Such studies include: in Nairobi [23] found a negative association between equity to debt ratio (EDR) and Return on equity (ROE).in Jordan [24] in Pakistan [15] who found that financial leverage has a statistically significant inverse impact on profitability at 99% confidence interval; in Tehran, Iran on the relationship among financial leverage and profitability [25]. Other examples include [26] in Thailand and [27] in India who established a positive relationship amid financial leverage and profitability.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Analytical studies entail processes of data collection, analysis, and concluding any given subject. They serve to comprehend, evaluate and enhance various aspects of the tourism sector (Shamaileh & Khanfar, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In the study conducted by Shamaileh and Khanfar (2014), they aimed to determine the financial leverage ratio for financial resources and the ratio of investment return on profitability in tourism companies operating in Jordan. Tourism companies traded on the Amman Stock Exchange were used as a sample in the study.…”
Section: Literature Reviewmentioning
confidence: 99%